2006
DOI: 10.1063/1.2206871
|View full text |Cite
|
Sign up to set email alerts
|

Pump-probe experiments at 1.54μm on silicon-rich silicon oxide waveguides

Abstract: Optical pump-probe measurements were performed on slab waveguides containing excess silicon in the form of nanoclusters or nanocrystals and erbium. The measurements were performed by prism coupling a 1.54 m probe beam into a waveguide formed by silicon-rich oxide and monitoring its intensity and temporal response as the waveguide was optically pumped from above with a chopped 477 nm excitation source. Induced absorption ͑losses͒ of the 1.54 m probe beam in erbium-doped and undoped silicon-rich silicon oxide wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
3
14
1
Order By: Relevance
“…They can rather be attributed to the excitons that are formed by electrons and holes in different Si-nc and thus separated by a large distance [128]. Similar long lifetime behaviors have been observed in ion-implanted samples, and explained in terms of the presence of specific charge traps within Si-nc or damaged nanocrystals [148].…”
Section: Sio2 (Cm 2 )supporting
confidence: 50%
“…They can rather be attributed to the excitons that are formed by electrons and holes in different Si-nc and thus separated by a large distance [128]. Similar long lifetime behaviors have been observed in ion-implanted samples, and explained in terms of the presence of specific charge traps within Si-nc or damaged nanocrystals [148].…”
Section: Sio2 (Cm 2 )supporting
confidence: 50%
“…In connection to silicon photonics, we should point out that the excited state absorption is substantial including the important 1.55 mm fiber optics communication wavelength. These results provide a more comprehensive picture than the reported experimental measurements [119][120][121] that are usually obtained at a single energy of the probe beam. Finally, it needs to be mentioned that for both intraband and excited state absorptions displayed in Figures 2.14 and 2.15, the high energy parts will be masked by the interband transition whenever it becomes energetically possible.…”
Section: Excited State Absorptioncontrasting
confidence: 49%
“…Recent experiments on excited state absorption concluded that more attention should be devoted to the role of the excitation conditions in the quest for the silicon laser [119][120][121]. For this reason, we consider another intraband absorption process where the system is under a continuous interband optical pumping that creates electrons and holes with excess energy.…”
Section: Excited State Absorptionmentioning
confidence: 99%
“…The explanation can be found either to excitons that are formed by electrons and holes separated by a large distance [6] or to the carrier trap associated with nanoclusters, as recently found by Forcales et al [34].…”
Section: B Pump and Probe Measurementsmentioning
confidence: 82%